Thermo properties of quaternary molten salt heat transfer fluid for heat recovery system - Tukimon, Mohd Faizal (2020)
In the context of the heat recovery system, the application of heat transfer fluid is one of the essential factors that can improve the efficiency of the system. According to the previous research, quaternary molten nitrate salt mixture has been proved to be an excellent heat transfer fluid in the heat recovery system. The objective of this study is to determine the formulation of quaternary molten nitrate salt mixture that has high heat capacity (Cp) with a low melting point. Besides that, the thermal properties and the heat transfer rate of the formulation have been determined through several testing. As for the methodology, the formulation of quaternary molten nitrate salt has been mixed and dried at 100oC for 24 hours to homogenize the mixture. At the beginning of the heating process, the mixture was heated up to 150oC and had been remained constant for four hours. Then, the temperature has risen up to 400oC. The mixing was done as the mixtures were cooled until it reached room temperature. From the result of DSC testing, the melting point for Sample 5 with a composition of 10wt% LiNO3 + 10wt% NaNO3 + 40wt% KNO3 + 40wt% Ca(NO3)2) has been verified to be below 100oC, which was 97.71oC with the highest heat capacity of 0.46J/goC. From TGA testing, the liquidus temperature and maximum thermal stability temperature of Sample 5 were detected at the temperature of 36.03 oC and 439.04oC respectively. For the heat transfer performance test, during the “Heater on” condition, it is shown that as the range of flow rate increased, the heat transfer rate has increased for all setting temperatures. As for the “Heater off” condition, Sample 5 has lost the least heat to the surrounding compared to other selected samples. In conclusion, Sample 5 with a composition of (10wt% LiNO3 + 10wt% NaNO3 + 40wt% KNO3 + 40wt% Ca(NO3)2) has been identified as an excellent formulation of quaternary molten nitrate salt that has potential to act as heat transfer fluid in the heat recovery system.